Case report: Delayed autologous tooth transplantation based on objective bone healing of the extraction socket (4-year follow-up) - Takahashi, Yusuke; Abe, Shotaro; Okamoto, Motoki; Tsujimoto, Tomomi; Murakami, Shumei; Hayashi, Mikako (Frontiers in Dental Medicine, 2023)
Autologous tooth transplantation is one of the best methods to replace a missing tooth when there is a suitable donor tooth. Tooth transplantation is mainly performed immediately after extraction because this is completed in a single surgery and donor tooth is transferred to fresh recipient site facilitated by remaining periodontal ligament. However, when transplantation is planned for severe recipient site with large bone defect surrounding the affected tooth, delayed transplantation is performed because of the mismatched size of donor tooth. When bone formation at the recipient site is gradually observed during wound healing, transplantation can be performed. However, estimated time for delayed transplantation has not been clearly determined because of the varied wound healing at recipient site. This case report demonstrates successful tooth transplantation 4 months after extraction by monitoring bone healing of the recipient site by computed tomography (CT). A male patient complained about occlusal pain in his mandibular molar. He had received the latest restoration after root canal treatment 10 years previously. Seven years later, he experienced slight spontaneous pain and consulted a private dental clinic. Radiographic examination revealed vertical root fracture and the dentist recommended tooth extraction, but he did not receive this suggestion. Several years later, he visited our hospital, and the bone resorption became much larger, and the surrounding bone was completely lost. Thus, it was decided autologous tooth transplantation several months later because of poor fit of the donor tooth using wisdom tooth. Sequential CT value was monitored during bone formation at the recipient site by multi-detector computed tomography. Four months later, CT value of the recipient site had gradually increased and tooth transplantation was performed. Fit of the donor tooth to the recipient site was still poor at the surgery, but it became better and tooth mobility decreased gradually. After performing root canal treatment, final full covered restoration was equipped. Review at 4 years after transplantation revealed the tooth showed no symptoms with no apical radiolucency. This case report suggests that delayed tooth transplantation can be performed after monitoring bone formation at the recipient site by X-ray or CT images.